(untitled) (Swiss Medical Weekly, 2022)
PURPOSE: To compare in-hospital treatment costs of aquablation and transurethral resection of the prostate (TURP) in the treatment of benign prostatic enlargement. PATIENTS AND METHODS: Patient data and procedural details were derived from a prospective database. In-hospital costs were calculated using detailed expenditure reports provided by the hospital accounts department. Total costs including those arising from surgical procedures, consumables, personnel and accommodation were analysed for 24 consecutive patients undergoing aquablation and compared with 24 patients undergoing TURP during the same period. Mean total costs and mean costs for individual expense items were compared between treatment groups with t-tests. RESULTS: Mean total costs per patient (± standard deviation) were higher for aquablation at EUR 10,994 ± 2478 than for TURP at EUR 7445 ± 2354. The mean difference of EUR 3549 was statistically significant (p <0.001). Although the mean procedural costs were significantly higher for aquablation (mean difference EUR 3032; p <0.001), costs apart from the procedure were also lower for TURP, but the mean difference of EUR 1627 was not significant (p <0.327). Medical supplies were mainly responsible (mean difference EUR 2057; p <0.001) for the difference in procedural costs. CONCLUSIONS: In-hospital costs are significantly higher for aquablation than for TURP, mainly due to higher costs of medical supplies for the procedure. This difference should be taken into consideration, at least in patients for whom the different side effect profiles of both treatments are irrelevant.